The effect of menaquinone-7 supplementation on vascular calcification in patients with diabetes: a randomized, double-blind, placebo-controlled trial. Issue 4 (6th August 2019) - Zwakenberg, S R; de Jong, P A; Bartstra, J W; van Asperen, R; Westerink, J; de Valk, H; Slart, R H J A; Luurtsema, G; Wolterink, J M; de Borst, G J; van Herwaarden, J A; van de Ree, M A; et al.
ABSTRACT: Background: Vitamin K occurs in the diet as phylloquinone and menaquinones. Observational studies have shown that both phylloquinone and menaquinone intake might reduce cardiovascular disease (CVD) risk. However, the effect of vitamin K on vascular calcification is unknown. Objectives: The aim of this study was to assess if menaquinone supplementation, compared to placebo, decreases vascular calcification in people with type 2 diabetes and known CVD. Methods: In this double-blind, randomized, placebo-controlled trial, we randomly assigned men and women with type 2 diabetes and CVD to 360 µg/d menaquinone-7 (MK-7) or placebo for 6 mo. Femoral arterial calcification at baseline and 6 mo was measured with 18 sodium fluoride positron emission tomography ( 18 F-NaF PET) scans as target-to-background ratios (TBRs), a promising technique to detect active calcification. Calcification mass on conventional computed tomography (CT) scan was measured as secondary outcome. Dephosphorylated–uncarboxylated matrix Gla protein (dp-ucMGP) concentrations were measured to assess compliance. Linear regression analyses were performed with either TBR or CT calcification at follow-up as the dependent variable, and treatment and baseline TBR or CT calcification as independent variables. Results: We randomly assigned 35 patients to the MK-7 group (33 completed follow-up) and 33 to the placebo group (27 completed follow-up). After the 6-mo intervention, TBR tended to increase in the MK-7 group compared with placebo (0.25; 95% CI: −0.02, 0.51; P  = 0.06), although this was not significant. Log-transformed CT calcification mass did not increase in the intervention group compared with placebo (0.50; 95% CI: −0.23, 1.36; P  = 0.18). MK-7 supplementation significantly reduced dp-ucMGP compared with placebo (−205.6 pmol/L; 95% CI: −255.8, −155.3 pmol/L). No adverse events were reported. Conclusion: MK-7 supplementation tended to increase active calcification measured with 18 F-NaF PET activity compared with placebo, but no effect was found on conventional CT. Additional research investigating the interpretation of 18 F-NaF PET activity is necessary. This trial was registered at clinicaltrials.gov as NCT02839044.